Pemanfaatan Terapi Komplementer untuk Mengurangi Mual Muntah pada Ibu Hamil Trimester I - Irma Maya Puspita (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2018)
Objective: Pregnancy is the intrauterine fetus's growth and development from conception until the onset of labor. One of the signs suffered by pregnant women in the first trimester is nausea and vomiting, which the occurrence of hyperemesis gravidarum can even exacerbate. Symptoms of nausea and vomiting during pregnancy can be overcome pharmacologically and non-pharmacologically. One of the non-pharmacological therapies that are simple, inexpensive, effective, and without adverse side effects is acupressure or massage at point 6 of the pericardium. This report aims to provide midwifery care to pregnant women with complementary acupressure therapy to reduce nausea and vomiting. Methods: The type of case report used is a case study. Results: After two weeks of acupressure therapy, nausea and vomiting experienced by Mrs. A are reduced.Conclusion: This case study concludes that acupressure can be used to reduce nausea and vomiting in first-trimester pregnant women. Therefore, health workers can apply acupressure in midwifery care, especially in reducing nausea and vomiting in first-trimester pregnant women